Jaume CAMPS BANSELL. (2021). Corazón educador. Un ensayo sobre la vocación a la enseñanza. - Galiano Moyano, Ana Carolina (2022)
The author of the book under review has extensively examined differentiated and personalized education and, in this work, directs his attention to the teacher as a fundamental pillar of the educational enterprise. Corazón educador. Un ensayo sobre la vocación a la enseñanza [The Educating Heart: An Essay on the Vocation of Teaching] (eBook ISBN: 9788418392207) constitutes an essay on the vocation of teaching that offers a reflective analysis of the ontological dimension of the teacher, considering the personal, interpersonal, and social dimensions inherent in pedagogical practice. In developing this study, Camps Bansell undertakes qualitative research based on testimonies gathered from both in-service teachers and pre-service teachers enrolled in Early Childhood and Primary Education degree programs. These accounts provide empirical grounding for the theoretical framework advanced throughout the work. Education is presented as a mystery that resists complete rational systematization; thus, an adequate understanding of its depth requires engagement with the interior dimension of the human person. Avoiding a romanticized conception of the teaching vocation, the author adopts instead a realist and humanistic perspective on education. From this standpoint, he articulates a sustained analysis centered on the vocation to teach, pedagogical love, and educational intuition. The most significant arguments pertaining to each of these dimensions are outlined below.